Endocrine disorders in obstructive sleep apnoea syndrome: A bidirectional relationship - Akset, Maud; Poppe, Kris Gustave; Kleynen, Pierre; Bold, Ionela; Bruyneel, Marie (Clinical endocrinology (Oxford), 2023)
Obstructive sleep apnoea (OSA) is a common disorder characterized by recurrent episodes of apnoea or hypopnea due to total or partial pharyngeal collapse and temporary upper airway obstruction during sleep. The prevalence of OSA is increasing and currently affects about 30% of men and 13% of women in Europe. Intermittent hypoxia, oxidative stress, systemic inflammation, and sleep fragmentation resulting from OSA can provoke subsequent cardiometabolic disorders. The relationships between endocrine disorders and OSA are complex and bidirectional. Indeed, several endocrine disorders are risk factors for OSA. Compared with the general population, the prevalence of OSA is increased in patients with obesity, hypothyroidism, acromegaly, Cushing syndrome, and type 1 and 2 diabetes. In some cases, treatment of the underlying endocrine disorder can improve, and occasionally cure, OSA. On the other hand, OSA can also induce endocrine disorders, particularly glucose metabolism abnormalities. Whether continuous positive airway pressure (CPAP) treatment for OSA can improve these endocrine disturbances remains unclear due to the presence of several confounding factors. In this review, we discuss the current state‐of‐the‐art based on the review of the current medical literature for key articles focusing on the bidirectional relationship between endocrine disorders and OSA and the effects of treatment. Screening of OSA in endocrine patients is also discussed, as it remains a subject of debate.